2003
DOI: 10.1111/j.1432-2277.2003.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of human papillomavirus infections with cutaneous tumors in immunosuppressed patients

Abstract: Besides immunosuppression and UV radiation, human papillomavirus (HPV) infection was also suggested to be involved in the development of non-melanoma skin cancer, the most common malignancy after transplantation. In this study we used a comprehensive PCR assay to analyze the prevalence of individual HPV types in different skin lesions from transplant and non-transplant patients. HPV DNA was detected more frequently in squamous cell carcinomas (SCCs) of transplant recipients (75%) than the same lesion was in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 21 publications
5
67
0
1
Order By: Relevance
“…The viral loads in the HPV-positive patients were low, ranging from one viral copy per y35 000 cells to three copies per cell, a trend also observed by other groups (Bens et al, 1998;Meyer et al, 2001;Weissenborn et al, 2005). We found that SK lesions harboured higher amounts of virus than AK; however, due to the small number of observations, this finding requires further investigation.…”
Section: Discussionsupporting
confidence: 59%
“…The viral loads in the HPV-positive patients were low, ranging from one viral copy per y35 000 cells to three copies per cell, a trend also observed by other groups (Bens et al, 1998;Meyer et al, 2001;Weissenborn et al, 2005). We found that SK lesions harboured higher amounts of virus than AK; however, due to the small number of observations, this finding requires further investigation.…”
Section: Discussionsupporting
confidence: 59%
“…Cutaneous ␤-HPVs are less studied. While ␤-HPVs appear to be part of the normal "skin flora" and infections are often asymptomatic, they can cause cutaneous warts, which undergo malignant progression in patients suffering from the rare genetic disease epidermodysplasia verruciformis (EV) or in systemically immune-suppressed organ transplant patients, particularly in sun-exposed areas of the body (2)(3)(4)(5). ␤-HPVs may also contribute to nonmelanoma skin cancers (NMSCs) in patients with a normal immune system, but this has not been formally proven.…”
mentioning
confidence: 99%
“…Weiterhin erwähnt wird in der Diskussion eine stattgehabte Therapie mit Chemotherapeutika in der Vorgeschichte der Patienten. Hier spielt neben dem immunsuppressiven Faktor der direkte kanzerogene Effekt dieser Medikamente eine Rolle (Hojo et al, 1999;Meyer et al, 2003 (Joseph et al, 1992;Weinstock, 1994). Bei Auftreten einer lokoregionären oder Fernmetastasierung kommt es zu einem relevanten Anstieg des Mortalitätsrisikos und zu einem…”
Section: % Wurde Für Die Lokalisation Am äUßeren Ohr Und In Der Perunclassified